TEORI HUMANISTIK DALAM PELAJARAN AKIDAH AKHLAK DI MAN 2 BIMA - Mulyani, Santi; Usman, Usman; Rappe, Rappe (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research aims to determine the application, describe the influence, identify inhibiting factors and overcome factors inhibiting the application of humanistic theory in moral learning at MAN 2 Bima. This research is qualitative with a case study methodology. The results of this research show that firstly, the application of humanistic theory in moral lessons is applied to the discussion method, secondly, the influence of the application of humanistic theory in moral aqidah lessons can be seen from students' ability to develop and explore their potential. Then, inhibiting factors include students who pay less attention and do not understand the lesson material. Then the average attendance is lower than others. Meanwhile, to overcome obstacles, teachers must use approaches and motivation